The Difficulties in Teaching Vocabulary Faced by the English Teacher at SMP Negeri 1 Luwuk - Yusniati N. Sabata; Vivi Damayanti Lagontang (English Education Study Program, 2020)
This research aims to find the difficulties faced by the English teacher in teaching vocabulary at SMP Negeri 1 Luwuk. The type of this research was descriptive qualitative. This research used an instrument to obtain data. The subjects of this study were the teachers at SMP Negeri 1 Luwuk.The data was collected through voice recording and then describe the data to find out the difficulties faced by the English teacher. Based on the results of the interview, the research draws the conclusion that the difficulties in teaching vocabulary came from students and the lack of available school facilities. Do not rule out the possibility of the teacher being a problem for themselves. The lack of response from the school about the development of facilities and student interest in teaching English was not only a problem for the teachers but also a challenge so that efforts to improve teaching techniques and methods become one of the solution and alternative that can be continued especially in teaching vocabulary so that the learning process can runs smoothly.